Globalization of sports / Gerhard Trosien - Trosien, Gerhard (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2013)
Globalization has a lot of definitions. It depends, what path it is discussed. In economic questions, there are especially trade of goods in ancient times. In modern time, that is not only goods are running around the world but the production branches are globalized long ago. Since there is work with a world wide web, many services are going globally – in reality and virtually. Sports have their own paths of going globalization. One important step has shown the re-activation of the new Olympic Games, which started 1896 in Athens/Greece. However, there are a lot of other sports, which not have been integrated into the Olympic Games and it is in the beginning, they went their own ways. Sailors, soldiers, students, merchants, and others (not to forget the aristocracy) brought their knowledge and habits to other countries and continents, so some special sports (mostly from Great Britain) spread out, where the British people went to, for examples: Rugby and Cricket. Moreover, the actual sports have established in most nations but they are not in the same intensity. Football of the European understanding is the most popular sports in the world today but it still plays a fifth wheel under the five major sports in the USA. American Football is number one there but it is never number one in another country of the world. Although the term “Americanization” indicates that a lot of trend sports coming from the USA even it is also the techniques to manage and to develop new markets internationally come from North America. As the result, after the fall of the “iron curtain” 1989 there are no barriers for the global free flow of goods, money, and individuals and the actual globalization of sports had experienced important changes and challenges.